MEDIATION AND LITIGATION IN UZBEKISTAN - Xayrulina Asal (European Science Publishing, 2024)
The institution of mediation appeared in Uzbek law relatively recently, in 2018, with the adoption of a special Law “On Mediation” . Over the next four years, fairly detailed regulation was developed to this law on a number of aspects, which include the consequences of the use of mediation for civil legal relations, the use of mediation in civil and economic court proceedings, and in the process of execution of judicial acts. The procedure for civil and economic proceedings is determined by the Constitution of the Republic of Uzbekistan, Law of the Republic of Uzbekistan “On Courts” , as well as procedural codes.